Answer:
7 , 11
Explanation:
Let the second number be 'x'
the first number = x - 4
Twice the second number : 2*x = 2x
5times first = 5*(x -4) = 5*x - 5*4 = 5x - 20
13 less than 5 times the first = 5x - 20 - 13 = 5x - 33
5x - 33 = 2x
Add 33 to both sides
5x - 33 + 33 = 2x +33
5x = 2x + 33
Subtract '2x'from both sides
5x - 2x = 2x - 2x + 33
3x = 33
Divide both sides by 3
![(3x)/(3)=(33)/(3)](https://img.qammunity.org/2022/formulas/mathematics/college/a51b3iuocsbqjs37lt61rn517frrcyig4h.png)
x = 11
First number = x - 4 = 11 - 4 = 7
The numbers are 7 , 11